2012
DOI: 10.1016/s0924-9338(12)74690-4
|View full text |Cite
|
Sign up to set email alerts
|

P-523 - Efficacy of psychoeducational family intervention for depression

Abstract: Studies on the efficacy of psychoeducational family intervention in patients with depression and their relatives are scarce. The effectiveness of this intervention in major depression has not been adequately investigated, probably because it is considered to be less burdensome by mental health professionals compared to schizophrenia or bipolar disorder. This study aims to test the efficacy of a psychoeducational family intervention on: 1) clinical status and social functioning of patients with major depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…We obtained 67 relevant articles for full-text review, and a further 50 studies were excluded for the following reasons: 2 were not RCTs, 32 did not include eligible patients, 11 did not include eligible interventions, and 5 were ongoing and did not provide any actual data. 62–66 Thus, out of 17 remaining records, 9 studies 27,28,3032,67–78 met the inclusion criteria for qualitative synthesis and 5 studies 72–78 met the inclusion criteria for the meta-analysis (supplementary Fig. 1)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We obtained 67 relevant articles for full-text review, and a further 50 studies were excluded for the following reasons: 2 were not RCTs, 32 did not include eligible patients, 11 did not include eligible interventions, and 5 were ongoing and did not provide any actual data. 62–66 Thus, out of 17 remaining records, 9 studies 27,28,3032,67–78 met the inclusion criteria for qualitative synthesis and 5 studies 72–78 met the inclusion criteria for the meta-analysis (supplementary Fig. 1)…”
Section: Resultsmentioning
confidence: 99%
“…Our findings, however, are the first to show quantitative results. Additionally, four studies 27,28,[30][31][32][67][68][69][70][71] identified during the present study that were not included in the meta-analysis report a significant effect of FPE on patients' depressive symptoms or general functioning. In particular, Shimazu et al reported high prevention of recurrence of MDD when applying FPE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have proven to reduce the psychological burden. Psychoeducation programs reduce the psychological burden on caregiver Alzheimer (Martín-Carrasco et al, 2009), reduce the burden of depressed families (Prisco et al, 2012), and reduce the psychological burden of the family caregiver diabetes mellitus (Ambarawati, 2015). Intervention-based cognitive-behavioral approaches can reduce the burden of care on Alzheimer's families (Marriott, 2000).…”
Section: Introductionmentioning
confidence: 99%